AFIKSĀSI FIL-KITĀB AL-MUQODDIMAH AL-HADRAMIYAH BINADHARIYYATI MUHAMMAD ALI AL-KHULLY - Fadzilah, Illa; Chotimah, Dien Nur (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
Affixation is adding morpheme to a word that may cause a change in the meaning. The presence of an affix can give new meanings to the words including those in Arabic language. Affixes consist of four divisions according to Muhammad Ali al-Hilli, prefix (initial), infix (middle), suffix (final), and confix (initial and final). The questions in this research: (1) What are the divisions of affixes in the Hadrami Introduction book? (2) How is the affixation process? This study used a descriptive qualitative approach, and the method of data collection used is reading and writing. The data analysis method used is data reduction, presentation, and conclusion. The results show 173 words with prefixes, 20 words with infixes, 12 words with suffixes, and ​​5 words with confixes. The total data analyzed is 205 words. The process of affixation of the words in the Hadrami Introduction includes the prefix added y, m, t, a, a ot, os ot to the beginning of nominative words, and infixes ie in the middle of the nominative case. The suffixes cover y at the end of the nominative words, and for confixes are by adding the hamza, taa, meem (initial) and wat, waw(final).